Hubungan Pengetahuan dengan Kepatuhan Perawat terhadap Pelaksanaan Pencegahan Risiko Jatuh pada Pasien Rawat Inap di RSUD Otanaha Kota Gorontalo - Nurayin Anenengo; Nurdiana Djamaluddin; Gusti Pandi Liputo (Transbahasa, 2025)
Nurses' knowledge of patient safety is essential to prevent errors or unwanted actions. Therefore, having good knowledge is crucial for nurses to improve their actions in the future. This study aims to determine the relationship between knowledge and nurses' compliance with the implementation of fall risk prevention in inpatient patients at Otanaha Regional Hospital, Gorontalo City. This research employs a qualitative method with statistical analysis using the Chi-Square test. The sampling technique used is Total Sampling, with a total of 40 nurses working in the Emergency Room (IGD), Internal Medicine Room 2, and Pediatric Room. The instrument used in this study is a questionnaire. The results show that after conducting a cross-sectional test, the obtained p-value is <0.05, specifically p-value <0.016. Thus, it can be concluded that there is a relationship between knowledge and nurses' compliance with the implementation of fall risk prevention in inpatient patients at Otanaha Regional Hospital, Gorontalo City. Based on this study, it is expected to enhance nurses' knowledge regarding fall risk prevention, thereby improving compliance in healthcare services, particularly in the application of patient safety.